Artes visuais afro-brasileiras na educação infantil: educando para as relações étnico-raciais - Bologna, Paula (Universidade Federal de São Carlos, 2019)
This undergraduate thesis investigates the insertion of afro-brazilian visual arts in Early Childhood Education. The principal goal of the research was to understand how a pedagogical work can be done with afro-brazilian visual arts in Early Childhood Education in order to educate for ethnic-racial relations, fighting racism. The specifics goals aimed to: understand how to work with afro-brazilian art in early childhood education in its complexity, studying and producing knowledge that contribute to a teaching practice that recognizes children as subject of rights; observe how the teacher develop a pedagogical work focused on Laws 10.639/03 and 11.645/2008, considering the development of society in its multiculturalities and educating for an racial ethnic conscience. The research has a qualitative approach and bibliographic character, was developed in continuity to the Scientific Iniciation research and is organized in five chapters. It was verified that there is a need to strengthen studies on afro-brazilian visual arts for pedagogical work in early childhood education since the graduation course and that the theme has essential relevance in the contexts of early childhood, Art and ethnic-racial relations studies aiming the realization of an anti-racist education.
Afro-Brazilian visual arts in early childhood education: educating for ethnic-racial relations
Keywords: Arte afro-brasileira; Afro-brazilian art; Educação Infantil; Early childhood education; Relações étnico-raciais; Ethnic-racial relations; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO